Perturbed Mucosal Immunity and Dysbiosis Accompany Clinical Disease in a Rat Model of Spondyloarthritis. Issue 9 (25th August 2016) - Asquith, Mark J.; Stauffer, Patrick; Davin, Sean; Mitchell, Claire; Lin, Phoebe; Rosenbaum, James T.
Abstract : Objective: The HLA–B27/β2 ‐microglobulin (β2 m)–transgenic (Tg) rat is a leading model of B27‐associated spondyloarthritis (SpA), and the disease is dependent on the presence of intestinal bacteria. Previous studies have shown that adult HLA–B27/β2 m–Tg rats have an altered intestinal microbiota. This study sought to better define the age‐dependent changes to both mucosal immune function and dysbiosis in this rat model of SpA. Methods: Intestinal contents were collected from wild‐type and HLA–B27/β2 m–Tg rats postweaning (ages 3 and 6 weeks), at disease onset (age 10 weeks), and after the establishment of disease (ages ≥16 weeks). The microbial community structure was determined by 16S ribosomal RNA sequencing and quantitative reverse transcription–polymerase chain reaction (qRT‐PCR). Mucosal and systemic Th1, Th17, and Treg cell responses were analyzed by flow cytometry, as was the frequency of IgA‐coated intestinal bacteria. Intestinal expression of inflammatory cytokines and antimicrobial peptides (AMPs) was determined by qRT‐PCR. Results: An inflammatory cytokine signature and elevated AMP expression during the postweaning period preceded the development of clinical bowel inflammation and dysbiosis in HLA–B27/β2 m–Tg rats. An early and sustained expansion of the Th17 cell pool was specifically observed in the cecal and colonic mucosa of HLA–B27/β2 m–Tg rats. Strongly elevated intestinal colonization of Akkermansia muciniphila and an increased frequency of IgA‐coated fecal bacteria were significantly associated with expression of HLA–B27 and arthritis development. Conclusion: HLA–B27/β2 m expression in this rat model renders the host hyperresponsive to microbial antigens from infancy. Early activation of innate immunity and expansion of a mucosal Th17 signature are soon followed by dysbiosis in HLA–B27/β2 m–Tg animals. The pathologic processes of perturbed mucosal immunity and dysbiosis strongly merit further study in both prediseased and diseased populations of patients with SpA.